The simultaneous high expression of Vα24, IFN-γ and FoxP3 characterizes the liver of children with type I autoimmune hepatitis - Ferreyra Solari, Nazarena Eugenia (2010)
The immunopathogenesis of type I autoimmune hepatitis (AIH-I) might involve the deregulation of different cellular processes. Here, we investigated the liver expression of selected cytokines and genes of regulatory cell populations in children both at diagnosis and during biochemical remission following immunosuppressive treatment (AIH-Ir). We found a higher Vα24, IFN-γ, FoxP3, IL-27p28, IL-12p40 and IL-21 expression at diagnosis as well as a positive correlation between IL-21 and transaminase levels. Interestingly, only IFN-γ and FoxP3 were decreased in AIH-Ir. An "AIH-I phenotype" (high Vα24, IFN-γ and FoxP3 expression at diagnosis) was observed in only 5 out of 22 AIH-Ir patients but not in controls. These results indicate a local deregulation of the innate and adaptive immune responses with an increased transcriptional activity of immunoregulatory cells at diagnosis. In addition, IL-21 is highlighted as a mediator of liver injury. AIH-Ir is characterized by a partial reversal of the deregulated response. © 2010 Elsevier Inc.